2018
DOI: 10.1016/j.iref.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Foreign direct investment and export quality upgrading in China's manufacturing sector

Abstract: Using a Melitz-type theoretical model of firm heterogeneity, we show that (i) the presence of foreign firms within an industry affects the industry export quality and (ii) the industry export quality is directly related to the industry export price. As the industry export price can be approximated by the industry export unit value, our work provides a rigorous theoretical justification for several empirical studies that use export unit value as a proxy for export quality. We then convert our theoretical model-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 37 publications
3
36
0
1
Order By: Relevance
“…The positive impact of IFDI on export sophistication is consistent with most previous studies (Harding and Javorcik, 2012;Zhu and Fu, 2013;Anwar and Sun, 2018). However, we should be cautious about making the conclusion that OFDI has no significant effect on China's export sophistication.…”
Section: Full Sample Regressionsupporting
confidence: 92%
See 2 more Smart Citations
“…The positive impact of IFDI on export sophistication is consistent with most previous studies (Harding and Javorcik, 2012;Zhu and Fu, 2013;Anwar and Sun, 2018). However, we should be cautious about making the conclusion that OFDI has no significant effect on China's export sophistication.…”
Section: Full Sample Regressionsupporting
confidence: 92%
“…The indirect effect occurs via the spillover effects of FDI on local fi rms. Therefore, the presence of FDI tends to generate a more sophisticated export structure in host countries (Harding and Javorcik, 2012;Zhu and Fu, 2013;Anwar and Sun, 2018). Another external factor affecting export sophistication is trade.…”
Section: Why Does Export Sophistication Matter?mentioning
confidence: 99%
See 1 more Smart Citation
“…By making use of GMM estimation applied to panel data over the 2005–07 period for six manufacturing industries in China, Sun and Anwar () find that foreign investment promotes domestic firms' involvement in exports through raising competition in the textile industry. Anwar and Sun () estimate a Melitz‐type model using panel data for the Chinese manufacturing sector and show that an increase in the presence of foreign direct investment leads to a significant increase in the export quality of China's manufacturing sector, especially in Hong Kong, Macao and Taiwan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent literature has shown that within-industry FDI entry has a large impact on export quality (e.g. Faruq, 2010;Harding and Jarvocik, 2012;Zhu and Fu, 2013;Amighini and Sanfilippo, 2014;Anwar and Sun, 2018). None of these studies have examined the across-industry effect of FDI liberalization policy yet.…”
Section: Introductionmentioning
confidence: 99%